Taxocenosis de las serpientes (Sauropsida: Squamata) de la provincia de Jujuy, Argentina - Burgos Gallardo, Freddy (2020)
In this work, we present a review on the composition and geographic distribution of the taxocenose of the snakes from Jujuy province (Argentina), based on the analysis of field-work records, specimens housed in public collections and literature revision. We analyzed a total of 819 records from 42 taxa belonging to Leptotyphlopidae (2), Boidae (2), Viperidae (3), Elapidae (1), Colubridae (3), and Dipsadidae (31). We discuss records relevant for conservation and biogeography of 18 species. Species richness is heterogeneous and variable depending on phytogeographic province and altitude. The highest numbers of species were recorded in the Yungas and Chaco, which reinforces the need to preserve and conserve these ecoregions in Jujuy. The models of potential distribution of viperid and elapid overlap with the most populated areas, thus indicating the need for the promotion of science divulgation to prevent conflicts with people and as a contribution to public health.